The risk of venous thromboembolism in patients with cirrhosis - Ambrosino, Pasquale; Tarantino, Luciano; Di Minno, Giovanni; Paternoster, Mariano; Graziano, Vincenzo; Petitto, Maurizio; Nasto, Aurelio; Di Minno, Matteo Nicola Dario (Thrombosis and Haemostasis, 2017)
Some studies suggest that patients with cirrhosis have an increased risk of deep venous thrombosis (DVT) and pulmonary embolism (PE). Unfortunately, available data on this association are contrasting. It was the objective of this study to perform a systematic review and meta-analysis of literature to evaluate the risk of venous thromboembolism (VTE) associated with cirrhosis. Studies reporting on VTE risk associated with cirrhosis were systematically searched in the PubMed, Web of Science, Scopus and EMBASE databases. Eleven studies (15 data-sets) showed a significantly increased VTE risk in 695,012 cirrhotic patients as compared with 1,494,660 non-cirrhotic controls (OR: 1.703; 95 %CI: 1.333, 2.175; P<0.0001). These results were confirmed when specifically considering the risk of DVT (7 studies, OR: 2.038; 95 %CI: 1.817, 2.285; P<0.0001) and the risk of PE (5 studies, OR: 1.655; 95 %CI: 1.042, 2.630; p=0.033). The increased VTE risk associated with cirrhosis was consistently confirmed when analysing nine studies reporting adjusted risk estimates (OR: 1.493; 95 %CI: 1.266, 1.762; p<0.0001), and after excluding studies specifically enrolling populations exposed to transient risk factors for VTE (OR: 1.689; 95 %CI: 1.321, 2.160; p<0.0001). Meta-regression models suggested that male gender may significantly impact on the risk of VTE associated with cirrhosis. Results of our meta-analysis suggest that cirrhotic subjects may exhibit an increased risk of VTE. This should be considered to plan specific prevention strategies in this clinical setting.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Deep venous thrombosis; pulmonary embolism; thromboembolism; thrombosis; cirrhosis